Pengembangan Buku Ajar Bold Make Up Look Pengantin Wanita Tapanuli Selatan pada Mata Kuliah Tata Rias Pengantin Indonesia Bagian Barat - Erianti, Lisa Rizki; Irtawidjajanti , Sri; Hidayah, Nurul (Universitas Pahlawan Tuanku Tambusai, 2025)
This study is a research and development (R&D) project that employs the 4D development model, which consists of Define, Design, Develop, and Disseminate stages. The product developed is a teaching book titled Bold Make Up Look for South Tapanuli Bride, intended as a learning medium for the course